ROLE AND FUNCTION OF SOCIAL MEDIA FOR SMALL AND MEDIUM-SIZE ENTERPRISE (SMES) IN BANDUNG, INDONESIA - Iston Dwija Utama, Rudy Aryanto, Mulyani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Emergence of social media makes a great opportunity for people to create and run business. This opportunity is also taken by the small medium-sized enterprise (SMEs) to expand their business. This research uses mixed research method i.e. quantitative and qualitative method; the quantitative method uses non-probability sampling approach, while qualitative method uses the exploratory approach by in-depth interview. Respondents of this research are owners of SMEs and social media expert. The results show that 73% SMEs run their business without any physical store; they provide good quality of content and deliver their strong value of proposition to attract their potential customers and standout compared to competitors. Many SMEs still can display their product in offline store through collaboration. Other findings show that contents in which the respondents share on social media mostly about marketing and sales, such as product information (84%), promotion (71%), and testimonial (46%) rather than general information (18%). Social media platforms that most respondents use are Facebook (86%), WhatsApp (86%), and Instagram (69%) as one of their marketing strategy tools. The implication of this research is that many SMEs are very dependent to the social media accounts and the role of marketing intermediaries becomes more powerful.